2019
DOI: 10.1016/j.jclepro.2019.02.169
|View full text |Cite
|
Sign up to set email alerts
|

Electrical enhancement period of solar photovoltaic using phase change material

Abstract: Temperature management in photovoltaic (PV) is critical for the power output. Phase Change Material (PCM) usage enables one to remove heat from the system and achieve enhanced electrical output. This study aims at finding the period of PV electrical enhancement, the increase in power and increase in electrical efficiency achieved using PCM under different working circumstances. Results suggest that as the angle of approach of wind changes from 75° to 0°, the electrical enhancement period elevates from 7.0 h to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…However, no work has been found in the literature where a phase change material has been integrated with a PV and hybrid renewable energy system. Phase change materials have the ability to cool down the PV [25] and store huge amount of energy in a latent form, consequently increasing the PV electrical efficiency [26]. The present study investigates how the integration of a phase change material with a PV panel will affect the optimization of the HRES, which thus has the potential to reduce the cost of energy.…”
Section: Introductionmentioning
confidence: 99%
“…However, no work has been found in the literature where a phase change material has been integrated with a PV and hybrid renewable energy system. Phase change materials have the ability to cool down the PV [25] and store huge amount of energy in a latent form, consequently increasing the PV electrical efficiency [26]. The present study investigates how the integration of a phase change material with a PV panel will affect the optimization of the HRES, which thus has the potential to reduce the cost of energy.…”
Section: Introductionmentioning
confidence: 99%
“…Latent heat thermal energy storage technology with PCMs is a promising way to improve the utilization rate of renewable energy, and ease the contradiction between energy supply and demand 1–5 . PCMs have many application potentials, such as continuous use of solar energy, waste heat recovery and utilization, cooling of electronics, mobilized thermal energy storage 6–14 . Inorganic hydrated salts PCMs have the advantages of high latent, stable phase change temperature, wide range of phase change temperature, and low price.…”
Section: Introductionmentioning
confidence: 99%
“…The system was found to be beneficial even with low-velocity conditions. By integrating micro-fins, PCM and nano-enhanced PCM, Sourav et al (2019) numerically and experimentally studied the effect of passive cooling technique (n-PCM) to lower PV temperature. Luo et al (2017) developed a PV-PCM device using shapestable composite paraffin PCM and found that form-stable composite PCM helps to control PV panels' temperature easily.…”
Section: Introductionmentioning
confidence: 99%